Turbin Angin Vertikal Model Savonius sebagai Alternatif Pemanfaatan Energi Baru Terbarukan - Iksan, M. Nor; Diana Alia; Henna Nurdiansari; Firdaus Sitepu (Jurnal Publikasi Teknik Informatika, 2025)
Renewable energy sources are energy sources formed through continuous processes, making their availability abundant and inexhaustible. Examples of renewable energy sources include solar energy, biomass energy, wind energy, hydropower, geothermal energy, wave energy, and others. The purpose of this study is to evaluate the efficiency and the ideal design of a Vertical Axis Wind Turbine (VAWT) as a sustainable alternative energy source. In addition, energy storage technology through renewable energy–based battery charging systems has also become an important focus, such as battery charging systems using solar panels that can be adapted to wind turbines. With the increasing demand for energy and the negative consequences of fossil fuel usage, there is a growing interest in finding more environmentally friendly renewable energy sources. Tests conducted in two different regions showed varying results, which were influenced by the geographical location of each area. This turbine is designed using PETG (Polyethylene Terephthalate Glycol) material, which has high transparency and strong resistance to chemicals. Based on the test results, the experiment in Nganjuk generated 13.2 Wh of power, while in Surabaya it generated 9.9 Wh. The spiral design allows the turbine to capture wind from multiple directions and reduce wasted wind flow, thereby maximizing the turbine’s ability to rotate the generator rotor.